The status of seagrass communities in the Truong Sa archipelago - Luong, Cao Van; Linh, Nguyen Manh; Hung, Vu Manh; Tien, Dam Duc; Thao, Dau Van; Lan, Tran Dinh (Vietnam Journal of Marine Science and Technology, 2020)
Seagrasses in Truong Sa archipelago have not been intensively studied and understood, even in some obviously progressive works recently published. It is essential to carry out much more researches to fill up understanding gaps of seagrasses in the area. In 2019, within the framework of the project coded KC09.29/16–20, two surveys were conducted for three selected islands (Truong Sa Lon, Thuyen Chai and Song Tu Tay) in the area, focusing on marine ecosystems including seagrass beds. Survey results in the selected islands show eight seagrass species (one new record), the estimated total distribution area of 1,190 ha, the total reserve of biomass reaching 7,417.2 tons.dry, equivalent to 11,432.8 tons.CO2.